Preparations for a New Gravimetric Geoid Model of New Zealand, and Some Preliminary Results - Amos, Matthew; Featherstone, Will (New Zealand Institute of Surveyors, 2003)
The rationale is given for a new gravimetric model of the New Zealand geoid to support a new vertical geodetic datum based on entirely different principles to the conventional use of tide gauges and geodetic levelling. The geoid model is currently being computed by Land Information New Zealand (LINZ) in close collaboration with the Western Australian Centre for Geodesy. The data to be used in this new geoid model comprise >40,000 land and >1.3M ship-track gravity data points, a 56 m-resolution digital elevation model (DEM), a 2' 2' grid of marine gravity anomalies derived from multimission satellite altimetry, and a hybrid global geopotential model derived from EGM96 and the new EIGEN-2 model. A preliminary geoid model has been computed from these data using spectral techniques with modified kernels, and comparisons with existing GPS-levelling data on the 13 different vertical datums used in New Zealand indicate an overall precision of ~ 35 cm, which can be improved with the more sophisticated data pre-processing currently underway. This preliminary geoid model has been used to estimate preliminary offsets among the 13 different vertical datums used throughout New Zealand. Importantly, the standard deviations are less than the computed offsets, which indicates that statistically significant offsets can be computed with the proposed approaches.